A new species of nurse-frog (Aromobatidae, Allobates) from the Juami River basin, northwestern Brazilian Amazonia - Simões, Pedro Ivo; Gagliardi-Urrutia, Giussepe; Rojas-Runjaic, Fernando J. M.; Castroviejo-Fisher, Santiago (Zootaxa, 2018)
We describe a new species of nurse-frog (Aromobatidae, Allobates) from northwestern Brazilian Amazon. Allobates juami sp. nov. is distinguished from similar congeneric species by the combination of the following characters: body-size range (snout-to-vent length 17.5–18.5 mm), lack of dark pigments on ventral surfaces of male specimens, dorsal color pattern (predominantly solid dark brown, but conspicuously light brown over snout and urostyle regions), presence of conspicuous pale dorsolateral and ventrolateral stripes, and presence of a diffuse pale paracloacal mark. The advertisement call of the new species lasts 2.5–5.1 s, contains 60–73 short notes (trills), and is emitted at an average rate of 13 notes per second within trills. Duration of silent intervals between notes ranges between 0.020–0.050 s, and the peak frequency of notes ranges from 4.59 to 5.47 kHz. The new species is currently known only from the type locality at Estação Ecológica Juami-Japurá (1.96455° S, 67.93579° W; 87 m a.s.l.).